Combination of Moderate Intensity Exercise and Rose Petals Yoghurt Alters Blood Pressure and Soluble Rage Level in High Advanced Glycation End Products Diet Induced Wistar Rat - Ratna, Ardhiyanti Puspita; Weningtyas, Anditri; Amelia, Widya Dana; Putra, Rexy Ichtiar Chesara (Newinera Publisher, 2024)
A diet high in advanced glycation end products (AGEs) has been linked to an increased risk of hypertension and other vascular degenerative diseases. Some intervention such as moderate intensity exercise, yogurt probiotic intake and anthocyanin supplementation had been conducted separately, and showed promising effects. The aim of this study is to analyse the effect of combining rose petal yoghurt and moderate intensity exercise in lowering blood pressure and sRAGE level in high AGEs diet induced model. This research was experimental study, using post test-only control group design. The animals that were used were white male rats (Rattus norvegicus) Wistar strain, divided into 5 groups. Group KN was given standar diet, KP was treated with high AGEs diet, KA was treated with high AGEs diet and combination of rose yoghurt and moderate exercise, KB was given high AGEs diet dan rose yoghurt, and KC group was treated with high AGEs diet and moderate exercise. After 12 weeks systolic and diastolic blood pressure was examined using Kent Scientific CODA blood pressure analyzer and sRAGE examined with ELISA technique. The result shows most decline in systolic and diastolic BP was at KC group which got a high AGEs diet and moderate intensity exercise. KC’s systolic BP was measured 120 ± 2.82 mmHg and diastolic at 77.25 ± 9.5 mmHg. The results of ELISA examination show KN has higher sRAGE level at 1865 ± 503.4 ng/L on the contrary KP has lower sRAGE level at 530 ± 78.6 ng/L.